Optimization of HRS-WC Mixture with Excavation Waste C and Beach Sand as Alternative Materials for Road Pavement - Asrul Saputra; Iqbal Iqbal; Ahmad Rijal Afandi; Fahmi Idris Hatala (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2026)
This study aims to evaluate the feasibility of incorporating Type C excavation waste and beach sand as alternative fine aggregate and filler materials in Hot Rolled Sheet–Wearing Course (HRS-WC) mixtures. A laboratory-based experimental approach was conducted to assess the mechanical performance and durability characteristics of the proposed mixtures. The results reveal that the mixture utilizing beach sand achieved the most balanced performance at an optimum bitumen content of 7.35%, with a stability value of 1755.78 kg and an air void (VIM) of 4.15%, fully complying with the 2018 Bina Marga specification. Moreover, the combination of excavation waste and beach sand fillers significantly improved moisture resistance, yielding the highest Index Retained Strength (IRS) of 127.39% and the lowest Cantabro loss of 0.59%. These findings indicate that the synergistic use of excavation waste and beach sand not only enhances mixture performance but also reduces the demand for natural aggregates and mitigates construction waste disposal. In practical terms, this approach supports a more sustainable, resilient pavement design for coastal infrastructure, where material scarcity and chloride exposure are major challenges. Overall, the study highlights the potential of locally available materials such as excavation waste and beach sand to produce HRS-WC mixtures that meet technical performance standards while promoting sustainable, cost-effective, and resource-efficient road construction in coastal regions.